Analysis of Employee Financial Management Behavior with Lifestyle as A Moderating Variable - Susilowati, Susilowati; Yudhanti, Ashari Lintang; Febry Fabian Susanto; Deasy Tantriana (Management Department, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Ampel Surabaya, 2026)
Objective – This research aims to examine the influence of financial literacy, financial attitude, and financial technology on the financial behavior of employees, with lifestyle as a moderating variable. This study is based on the phenomenon of many Indonesian civil servants falling into debt, reflecting a lack of financial literacy and proper financial management behavior. The study addresses the importance of financial awareness to prevent consumptive lifestyles exacerbated by the use of financial technology (fintech). Design/methodology/approach – Using a quantitative approach, this research employs Partial Least Squares (PLS) Structural Equation Modeling (SEM) analysis on 196 respondents drawn from the civil servant population of UIN Sunan Ampel Surabaya. The study analyzes the variables of financial literacy, financial attitude, financial technology, and lifestyle in relation to financial behavior. Findings – The findings reveal that financial literacy and financial attitude do not significantly affect financial behavior. However, financial technology has a positive and significant impact on financial behavior. Moreover, while lifestyle does not moderate the relationship between financial literacy or financial attitude and financial behavior, it does moderate the relationship between financial technology and financial behavior. This indicates that the influence of fintech on financial behavior is stronger among individuals whose lifestyle aligns with digital and technology-driven practices. Research limitations/implications – This research was conducted within a single institution in Indonesia, which may limit the generalizability of the findings. Future research could examine similar models across different institutions or countries, and explore additional moderating or mediating variables such as financial self-efficacy or digital literacy. Practical implications – The study emphasizes the importance of promoting effective use of fintech tools tailored to users' lifestyles. Organizations should focus on fostering digital financial behavior while acknowledging that financial knowledge and attitude alone may not lead to behavioral change. Practical financial literacy programs should be designed alongside initiatives that promote healthy lifestyle habits. Originality/value – This research uniquely integrates the moderating role of lifestyle in the relationship between financial technology and financial behavior. The study contributes to the growing literature on personal financial management by showing that digital tools are more effective when aligned with users' everyday habits and preferences.